2017
DOI: 10.1159/000475672
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraoperative Computed Tomography during Deep Brain Stimulation Procedures: Comparison with Postoperative Magnetic Resonance Imaging

Abstract: Objective: To determine the accuracy of intraoperative computed tomography (iCT) in localizing deep brain stimulation (DBS) electrodes by comparing this modality with postoperative magnetic resonance imaging (MRI). Background: Optimal lead placement is a critical factor for the outcome of DBS procedures and preferably confirmed during surgery. iCT offers 3-dimensional verification of both microelectrode and lead location during DBS surgery. However, accurate electrode representation on iCT has not been extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 489 publications
(28 citation statements)
references
References 21 publications
(31 reference statements)
2
25
1
Order By: Relevance
“…Some centers utilize intraoperative computed tomography (iCT) to verify accuracy of lead placement. This is done through the fusion of the iCT scan with the preoperative MRI scan after intracranial electrode implantation . Meanwhile, other centers use an interventional MRI (iMRI) to guide placement of DBS electrodes .…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Some centers utilize intraoperative computed tomography (iCT) to verify accuracy of lead placement. This is done through the fusion of the iCT scan with the preoperative MRI scan after intracranial electrode implantation . Meanwhile, other centers use an interventional MRI (iMRI) to guide placement of DBS electrodes .…”
Section: Surgical Techniquementioning
confidence: 99%
“…The modality of intraoperative image verification of lead accuracy makes a difference. For example, target confirmation through fusion with an iCT scan in asleep DBS surgery appears to shorten the duration of surgery . While there are few published research studies using intraoperative MRI , one reported advantage is that the intraoperative (or interventional) MRI (iMRI) approach uses near real‐time acquisition of images to prospectively guide both trajectory planning and the intended targets verification before electrode placement .…”
Section: Surgical Techniquementioning
confidence: 99%
“…In some centers, intraoperative computed tomography (iCT) during surgery is used to verify the accuracy of lead placement (Table 1). This is achieved through fusion of iCT scans and preoperative MRI scans after intracranial electrode implantation [31,37,41,44,47]. In awake DBS surgery with MER guidance, iCT provides useful information, such as hemorrhage and a general idea of electrode location when fused with preoperative MRI [21].…”
Section: Intraoperative Ctmentioning
confidence: 99%
“…Currently, there are two surgical treatments available for people living with PD—deep brain stimulation (DBS) and surgery performed to insert a tube in the small intestine, which delivers a gel formulation of carbidopa/levodopa (Duopa™) [ 74 , 75 , 76 , 77 ]. In DBS, surgery is performed to insert electrodes into a targeted area of the brain, using MRI and recordings of brain cell activity during the procedure.…”
Section: Introductionmentioning
confidence: 99%